RESEARCH OF INFLUENCE OF PERFORATION TO REDUCE PULSATION LOADS ACTING ON THE AERODYNAMIC CONTROL SURFACES - V. T. Kalugin; A. S. Epikhin; P. A. Chernukha (Научный вестник МГТУ ГА, 2016)
The research of unsteady vortex flow influence on the aerodynamic control and stabilizing surfaces is carried out. There are defined pulsation aerodynamic characteristics of flight controls with using the open software OpenFoam. The results of the numerical calculations of flow around brake flap and set behind him vertical stabilizer. The pulsation load on the pitching-stabilizer, due to the presence of a brake flap installed at different angles of deflection was calculated. To reduce the pulsation load offered the option of perforated brake flap.